Peningkatan perkembangan kognitif anak usia dini melalui kegiatan bermain Puzzle di TK Diponegoro 171 Windujaya - Dewinta Kurnietin; Tugiyono Tugiyono; Muhaimi Mughni Prayogo (Indonesian Journal of Learning and Educational Studies, 2025)
This study investigates the use of educational puzzle games to enhance cognitive development in Group B students at TK Diponegoro 171 Windujaya. Observing low cognitive performance among the children, the teacher initiated classroom action research during the 2024/2025 academic year to improve learning quality through puzzle-based activities. The research followed Kemmis and McTaggart’s (1988) classroom action research model, utilizing descriptive qualitative and quantitative methods over two cycles. Participants included 22 children that consist of 7 boys and 15 girls. Data were collected through observation and documentation. Results indicated a significant improvement in cognitive development, increasing from 71% in Cycle I to 87% in Cycle II. These findings demonstrate that puzzle-based learning activities effectively support young children’s cognitive growth. Furthermore, this approach may be applied in other educational settings to enrich teaching practices and promote further research into cognitive development through puzzle play.